Public health journals’ requirements for authors to disclose funding and conflicts of interest: a cross-sectional study - Karim N. Daou; Maram B. Hakoum; Assem M. Khamis; Lama Bou-Karroum; Ahmed Ali; Joseph R. Habib; Aline T. Semaan; Gordon Guyatt; Elie A. Akl (BMC Public Health, 2018)
Abstract Background Public health journals need to have clear policies for reporting the funding of studies and authors’ personal financial and non-financial conflicts of interest (COI) disclosures. This study aims to assess the policies of public health journals on reporting of study funding and the disclosure of authors’ COIs. Methods This is a cross-sectional study of “Public, Environmental & Occupational Health” journals. Teams of two researchers abstracted data in duplicate and independently using REDCap software. Results Of 173 public health journals, 155 (90%) had a policy for reporting study funding information. Out of these, a majority did not require reporting of the phase of the study for which funding was received (88%), nor the types of funding sources (87%). Of the 173 journals, 163 (94%) had a policy requiring disclosure of authors’ COI. However, the majority of these journals did not require financial conflicts of interest disclosures relating to institutions (75%) nor to the author’s family members (90%) while 56% required the disclosure of at least one form of non-financial COI. Conclusions The policies of the majority of public health journals do not require the reporting of important details such as the role of the funder, and non-financial COI. Journals and publishers should consider revising their editorial policies to ensure complete and transparent reporting of funding and COI.